From preliminary aircraft cabin design to cabin optimization - Mihaela Niţă; Dieter Scholz (Deutscher Luft- und Raumfahrtkongress 2010, 2010)
This paper conducts an investigation towards main aircraft cabin parameters . The aim is two-fold : First, a handbook method is used to preliminary design the aircraft cabin. Second, an objective function representing the "drag in the responsibility of the cabin" is created and optimized us i ng both an analytical approach and a stochastic approach . Several methods for estimating wetted area and mass are investigated. The results provide optimum values for the fuselage slenderness parameter (fuselage length divided by fuselage diameter) for civil transport aircraft. For passenger aircraft, cabin surface area is of importance. The related optimum slenderness parameter should be about 10. Optimum slenderness parameters for freighters are lower: about 8 if transport volume is of importance and about 4 if frontal area for large items to be carried is of importance.
Keywords: Luftfahrt; Luftfahrzeug; Passagierflugzeug; Flugzeugkabine; Flugzeugbau; Optimierung; Genetischer Algorithmus; Aerodynamik; Aeronautics; Airplanes; Mathematical optimization; Aircraft cabins; Aerospace engineering; Spreadsheets; Genetic algorithms; Aerodynamics; wetted area; drag; mass; fuselage; cabin; diameter; cross section; length; slenderness; cabin surface area; frontal area; passenger; seat; aisle; cargo; baggage; optimization